Penatalaksanaan Fisioterapi Pada Kasus Cervical Root Syndrome Di RSUD Dr. Moewardi Surakarta - Widodo, Slamet; , Totok Budi Santoso, S.Fis., MPH (2015)
Background : Cervical root syndrome is an abnormal condition resulting from irritation or cervical nerve root compression due to trauma, athritis or bulging discs in the neck area invertebralis. Symptoms of pain Lehar that spreads to the shoulders, upper and lower limbs, parasthesia, muscle spasm or weakness of the muscles innervated. Objective : To find out how big the problems that arise necessary to check eg pain with Descriptive Verbal Scale (VDS), decreased range of motion with midline. In addressing these problems modalities Micro Wave Diathermy (SWD), Transcutaneus Electrical Nerve Stimulation (TENS) and exercise therapy (TL) can be obtained by a decrease pain, increase range of motion. Results : After treatment carried out during the six assessment results obtained as follows: the VDS pain: pain motion becomes T6 Tl = 5 = 3, tenderness T1 = 4 becomes T6 = 2, the range of motion in flexion movement midlen T1 = 2 to T6 = 5, extension into T6 T1 = 3 = 5, laterofleksi dextra T1 = 6 to T6 = 8, the left laterofleksi be T6 T1 = 4 = 8, rotation dextra T1 = 10 to T6 = 11, the rotation of the left T1 = 10 to T6 = 11. Conclusion : The benefits of modalities Micro Wave Diathermy (SWD), Transcutaneus Electrical Nerve Stimulation (TENS ) and exercise therapy (TL) in Cervical Root Syndrome is that the interference of pain and limitation of motion can be handled. Suggestions in this case for the patient to carry out treatment in accordance with a program that has been done and the routine in the program at home in order to obtain the result of a perfect treatment. Physiotherapy should establish good cooperation with the patient and the medical side as well as the need to hold further research to determine what is the best modality for conditions Root Cervical Syndrome.